What fish are saying : strange sounds in the ocean - Pendreigh, Kirsten (Sourcebooks Explore, 2025)
"A rhyming nonfiction picture book about the cutting-edge science of how fish talk to each other in the ocean. Follow along with one little shellfish to discover cutting-edge, under-the-sea science! Did you know that deep in the ocean, fish are loud? Scientists have recently discovered that fish and shellfish grunt and groan, crackle and cluck, and even burp burp and boop to communicate. They warn each other, woo each other, and welcome each other with all kinds of sounds, making the ocean quite noisy! Dive into a fascinating underwater adventure that guides readers through the surprisingly loud world beneath the waves"--